It's easy, right?

Geometry Level 3

If tan θ = n tan ϕ \tan \theta = n\tan\phi , then the maximum value of tan 2 ( θ ϕ ) { \tan }^{ 2 }(\theta -\phi ) is equal to:

( n + 1 ) 2 4 n \frac { { (n+1) }^{ 2 } }{ 4n } ( n 1 ) 2 2 n \frac { { (n-1) }^{ 2 } }{ 2n } ( n + 1 ) 2 2 n \frac { { (n+1) }^{ 2 } }{ 2n } ( n 1 ) 2 4 n \frac { { (n-1) }^{ 2 } }{ 4n }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Oct 27, 2018

tan 2 ( θ ϕ ) = ( tan θ tan ϕ 1 + tan θ tan ϕ ) 2 Given that tan θ = n tan ϕ = ( n 1 ) 2 tan 2 ϕ ( 1 + n tan 2 ϕ ) 2 Let x = tan 2 ϕ = ( n 1 ) 2 x ( 1 + n x ) 2 = ( n 1 ) 2 n ( 1 + n x 1 ( 1 + n x ) 2 ) = ( n 1 ) 2 n ( 1 1 + n x 1 ( 1 + n x ) 2 ) = ( n 1 ) 2 n ( 1 4 ( 1 1 + n x 1 2 ) 2 ) Note that ( 1 1 + n x 1 2 ) 2 0 ( n 1 ) 2 4 n Equality occurs when x = 1 n \begin{aligned} \tan^2 (\theta - \phi) & = \left(\frac {\tan \theta - \tan \phi}{1+\tan \theta \tan \phi} \right)^2 & \small \color{#3D99F6} \text{Given that }\tan \theta = n \tan \phi \\ & = \frac {(n-1)^2\tan^2 \phi}{(1+n\tan^2 \phi)^2} & \small \color{#3D99F6} \text{Let }x = \tan^2 \phi \\ & = \frac {(n-1)^2x}{(1+nx)^2} \\ & = \frac {(n-1)^2}n \left(\frac {1+nx - 1}{(1+nx)^2}\right) \\ & = \frac {(n-1)^2}n \left(\frac 1{1+nx}- \frac 1{(1+nx)^2}\right) \\ & = \frac {(n-1)^2}n \left(\frac 14 - \left(\frac 1{1+nx}- \frac 12\right)^2 \right) & \small \color{#3D99F6} \text{Note that }\left(\frac 1{1+nx}- \frac 12\right)^2 \ge 0 \\ & \le \boxed {\dfrac {(n-1)^2}{4n}} & \small \color{#3D99F6} \text{Equality occurs when }x = \frac 1n \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...